Miles over mind: Transnational death and its association with psychological distress among undocumented Mexican immigrants. Issue 6 (2nd June 2020) - Garcini, Luz M.; Galvan, Thania; Brown, Ryan; Chen, Michelle; Klonoff, Elizabeth A.; Ziauddin, Khadija; Fagundes, Christopher P.
Abstract: Objective: This study examined the association between transnational death and psychological distress among undocumented Mexican immigrants. The Minority Stress Model and a disenfranchised grief perspective were used as frameworks for this study. Method: Respondent driven sampling (RDS) was used to collect data from clinical interviews with 248 undocumented Mexican immigrants residing near the US–Mexico border. Results: After controlling for relevant covariates, experiencing transnational death was a significant predictor of clinically significant distress in this at-risk population. Conclusions: Our findings underscore the need to contextualize transnational death among undocumented immigrants from a perspective of disenfranchised grief that requires the development of contextually and culturally sensitive interventions aimed at addressing the high prevalence of transnational death and its associated distress in this marginalized population.